Queer Literature and Gender Sensitivity of Senior High School Students - De Jesus, Aira; Dorado, Jaya; Biag, Eula; Durante, Jerlie Vill; Llames, Joshua Eriberto Miguel (International Journal of Arts, Sciences and Education, 2022)
The paper explores the possibilities of implementing queer literature as a reading material of senior high school students in promoting gender sensitvity. Descriptive-correlational method was used. Three academic strands were selected as the participants of the study namely, ABM, HUMSS and STEM. There were sixty (60) respondents who answered the survey questionnaire through Google Form. Also, the Pearson Correlation data analysis was considered. To sum it up, the analysis shows that students are moderately exposed to queer literature and they are highly gender sensitive. And, the profile of the respondents has no significant relationship with the level of exposure to queer literature and the level of gender sensitivity of the students except the profile in terms of strand. Additionally, it can be inferred from this study that there is no significant relationship between the grade level and the level of exposure to queer literature as well as between the gender and the level of gender sensitivity. However, the relationship between the exposure to queer literature and the level of gender sensitivy is strong which implies that the exposure to queer literature plays a big role in promoting gender sensitivity among the students. Thus, the study concludes that further exposure to queer liteture makes the students gender sensitive. Moreover, the exposure of queer literature to the students shall be ecouraged to promote gender sensitivity. On top of that, researchers strongly recommend that curriculum implementers embrace queer literature as a reading material of the students in the senior high school.